Features of the course of post-COVID-19 primary and recurrent herpetic keratitis - G.I. Drozhzhyna; K.V. Sereda; N.I. Khramenko (Journal of Ophthalmology)
Purpose: To assess the features of the course of post-COVID-19 primary and recurrent herpetic keratitis (HK). Material and Methods: Medical records of 70 patients (83 eyes) with post-COVID-19 HK were reviewed. The patients were divided into two groups: group 1 with primary HK (26 patients; 30 eyes) and group 2 with recurrent HK (44 patients; 53 eyes). COVID-19 severity was defined as mild (without evidence of viral pneumonia), moderate (pneumonia not treated at the intensive care unit (ICU)) and severe (treatment at the ICU). Levels of total vitamin D, and immunoglobulin G (IgG) against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein, herpes simplex virus (HSV)-1/2, cytomegalovirus (CMV) and Epstein-Barr nuclear antigen (EBNA) in venous blood were assessed. Results: Dendritic HK and ulcerative necrotizing HK were more common in patients with primary keratitis than in recurrent keratitis (20.7% vs 2% and 41.2% vs 15.6%, respectively). Non-necrotizing stromal HK was more common in the latter patients than in the former patients (82.4% vs 37.9%, respectively) and was the most common form of post-COVID-19 HK in both groups. Ulcerative necrotizing HK was more common in patients with primary HK than in patients with recurrent HK (41.4% vs 15.6%, respectively) and was mainly observed after severe COVID-19. In patients with ulcerative necrotizing HK, the level of HSV IgG was 1.6 times higher than in patients with epithelial HK, and 1.5 times higher than in patients with non-necrotizing stromal HK. Elevated anti-VZV, anti-EBNA, and anti-CMV IgG levels were found in 93.2%, 76.4%, and 86.4%, respectively, of the examined patients. Conclusion: SARS CoV 2 infection may be a potential risk factor for HSV reactivation from latency and primary or recurrent HK, with an increase in the frequency of bilateral ocular lesions and stromal forms of HK. The ophthalmologist must be aware of this ocular complication in COVID 19–infected cases, which may present either during acute or recovery phase of the illness; it mostly occurs in severely infected patients.